2021
DOI: 10.1002/deo2.42
|View full text |Cite
|
Sign up to set email alerts
|

Extensive mucosal sloughing of the small intestine and colon in a patient with severe COVID‐19

Abstract: Patients with coronavirus disease 2019 (COVID‐19) primarily cause respiratory symptoms. However, gastrointestinal (GI) symptoms can also occur. The endoscopic characteristics of the GI tract in COVID‐19 patients remain unclear. We herein report a 62‐year‐old male with severe COVID‐19 who needed multidisciplinary treatment, including extracorporeal membrane oxygenation (ECMO). Despite the improvement in his respiratory status, GI bleeding developed. Capsule endoscopy and colonoscopy revealed extensive mucosal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…Our institution reported that abdominal pain is a risk factor for severe disease outcomes in COVID-19 ( 2 ). We have also reported a rare case of severe gastrointestinal mucosal damage during the treatment of COVID-19 pneumonia ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our institution reported that abdominal pain is a risk factor for severe disease outcomes in COVID-19 ( 2 ). We have also reported a rare case of severe gastrointestinal mucosal damage during the treatment of COVID-19 pneumonia ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 , [24] , [25] , [26] , [27] ] One case report describes diffuse small intestinal mucosal sloughing, reminiscent of graft-versus-host disease, detected by capsule endoscopy. [ 28 ] However, a significant number of upper GI tract examinations are normal (29.9% in one series). [ 24 ] Colonoscopic examination in COVID-19 patients has shown ischemic colopathy, non-specific erythema, non-specific colonic inflammation, and ulcerative inflammatory colitis.…”
Section: Gastrointestinal and Hepatobiliary Manifestations Of Covid-19mentioning
confidence: 99%
“…[ 11 ] In the case mentioned earlier with small intestinal mucosal sloughing by capsule endoscopy, colonic biopsies showed edema, erosions, infiltration by lymphocytes, and epithelial cell apoptosis. [ 28 ] Finally, a report by Westerhoff and colleagues [ 88 ] describes ileal biopsies in a patient with COVID-19 that demonstrated active ileitis, villous lymphocytosis, increased goblet cells in the villi, and crypt hyperplasia. Neither ISH nor NGS was positive for SARS-CoV-2.…”
Section: Pathologic Findings In the Gastrointestinal Tract And Livermentioning
confidence: 99%
“…The use of artificial organs has become a preferred and safer curing method. Especially in the treatment of COVID-19, ECMO membranes (artificial lungs) have become the most effective method for the treatment of severe cases [9] , [10] .…”
Section: Membranes For Artificial Organsmentioning
confidence: 99%
“…Especially for PMP, the raw material and preparation technology are monopolistic. In addition to the above three generations of membrane materials, in the latest research, fluoropolymers have been reported to significantly improve the service life by reducing the surface energy during gas exchange and are expected to become a new research direction for the preparation of ECMO membranes [9] , [10] . In Park’s work, the as-prepared poly(vinylidene-co-hexafluoropropylene) membrane was coated with Hyflon AD60X (which is a typical fluoropolymer with an extremely low surface energy), displaying a repulsion for both water and blood without hemolysis in a long term.…”
Section: Membranes For Artificial Organsmentioning
confidence: 99%